Emotional Intelligence as a Mediator between Personality Traits and Digital Literacy in Enhancing Customer-Oriented Behavior among Nursing Students in Malaysia - Misron, Aervina; Hee, Ong Choon; Zandi, GholamReza (International Review of Management and Marketing, 2025)
The quality of healthcare service delivery is increasingly scrutinized, with a significant focus on the role of nurses in ensuring patient satisfaction. Customer-oriented behavior (COB) among nursing professionals plays a critical role in shaping these outcomes. This study examines the impact of Big Five personality traits and digital literacy on COB among Malaysian nursing students, with emotional intelligence (EI) serving as a mediating variable. Using a sample of 437 nursing students from public nursing colleges in Malaysia, data was collected via stratified random sampling and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). Results indicated that digital literacy significantly predicted COB, while emotional intelligence mediated the relationship between certain personality traits (openness, conscientiousness, and neuroticism) and COB. These findings highlight the importance of integrating emotional intelligence and digital literacy into nursing education to enhance service delivery in Malaysia’s public healthcare sector. The stud’s implications for nursing curricula and recruitment are discussed, providing a framework for improving customer-oriented behavior through targeted training and development.